2012
DOI: 10.1002/hed.23116
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of expression of cyclooxygenase‐2, vascular endothelial growth factor, and epidermal growth factor receptor in nasopharyngeal carcinoma

Abstract: High expression of COX-2, VEGF, and EGFR were independent adverse prognostic factors for long-term outcomes in nonmetastatic NPC independent of clinical stage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
52
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(55 citation statements)
references
References 61 publications
3
52
0
Order By: Relevance
“…Although 1 patient in the radiation-sensitive group revealed increased expression of EGFR, the staining intensity of the tissue derived from the patient was relatively decreased compared with that from the patients of the radiation-resistant group. This result supported studies by Pan et al (34) and Ma et al (35), which demonstrated that EGFR overexpression was associated with radiation resistance in head and neck cancer, and prognostically associated with a decreased local control rate and survival. Multiple studies have revealed that ~80% of primary NPC biopsies demonstrate increased expression of EGFR (36,37).…”
Section: Discussionsupporting
confidence: 90%
“…Although 1 patient in the radiation-sensitive group revealed increased expression of EGFR, the staining intensity of the tissue derived from the patient was relatively decreased compared with that from the patients of the radiation-resistant group. This result supported studies by Pan et al (34) and Ma et al (35), which demonstrated that EGFR overexpression was associated with radiation resistance in head and neck cancer, and prognostically associated with a decreased local control rate and survival. Multiple studies have revealed that ~80% of primary NPC biopsies demonstrate increased expression of EGFR (36,37).…”
Section: Discussionsupporting
confidence: 90%
“…Finally, we enrolled 15 eligible articles containing survival outcomes [11,[15][16][17][18]22,[24][25][26][27][28][29][30][31][32][33][34][35], among which two studies were written in Chinese [22,33], whereas the others were English articles. These eligible studies were published from 2002 to 2012.…”
Section: Eligible Studiesmentioning
confidence: 99%
“…Samples from North Asia (China, Korea, Japan, and Singapore) [15][16][17]22,24,25,[27][28][29][30][31][32][33][34] were yielded for HRs. The result suggested that EGFR was associated with NPC prognosis, and HR for OS was 2.05 [1.17, 3.60], (I2 = 92%, P = 0.…”
Section: Subgroup Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…In the European population heterogeneity was also significant (I 2 = 67%). The hazard ratios from Leong et al [16,], Fuji et al [17], Ma et al [18,], Pan et al [19], TaheriKadkhoda et al [20], Cao et al [21], Leong et al [16] and Fang [21] et al were taken with permission from the study by Sun et al [14]. The HR of Krikelis et al [22] was calculated by the authors using IBM SPSS 20.0 statistical software.…”
Section: Overall Survivalmentioning
confidence: 99%